Islam, architecture & urban planning - Omer, Spahic (Arah Pendidikan Sdn Bhd., 2009)
This book titled “Islam, architecture & urban planning” is a compilation of studies on the relationship between spirituality and built environment in Islam. The book consists of twelve chapters representing twelve separate studies nine of which were presented in one national and eight international conferences and symposiums held in six different countries. In addition, the substance of several chapters is based partly or completely on the material already published in the form of either academic journal papers or chapters in another books produced by the same author. The book covers a number of major aspects of Islamic built environment, such as: Islam on the enterprise of building, Islamic architecture, Islamic urban planning and development, environmental protection, Islam and housing, and Islamic aesthetics. The nature of the book’s studies is a conceptual or philosophical rather than an empirical one. The chief objective of the book is to increase the Muslim awareness as to the significance of integrating the elements of spirituality into the spheres of built environment. The book also aspires to serve as a starting point for such an integration. There are very few scholarly studies conducted on the theme of integrating the Islamic spirituality into built environment. Thus, another objective of this book is to partly fill up a glaring academic gap and to spur the interest of both the Muslim professionals and Muslim scholars on such an important subject matter inviting them that they all contribute their respective expected shares. Certainly, there are many studies that treat the subject of Islamic built environment with its many aspects but only from certain limited cultural, social or historical perspectives. It is not easy to find a comprehensive study that treats the matter from a broader spiritual perspective, integrating the same with and thus adding a new dimension to the rest of social, cultural and historical perspectives. This book is an attempt towards that direction.